High-pressure phase behaviour of poly(D-lactic acid), trichloromethane, and carbon dioxide ternary mixture systems - Im, Taehyun; Gwon, JungMin; Kim, Soo Hyun; Shin, Hun Yong; Kim, Hwayong (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2015)
The high pressure phase behaviour of poly(D-lactic acid) (M-w = 359,000), trichloromethane, and carbon dioxide ternary mixture systems is presented in this study. Cloud and bubble point pressures were measured using a variable volume view cell at temperatures (313.15 to 363.15) K and pressures up to 33.6 MPa. The hybrid equation of state for the polymer-carbon dioxide system was used to correlate the experimental results. The van der Waals one-fluid mixing rule with three adjustable binary interaction parameters was used for all correlations. The binary parameters were optimised using the simplex method algorithm. (C) 2015 Published by Elsevier Ltd.